A community cohort study about childhood social and economic circumstances: racial/ethnic differences and associations with educational attainment and health of older adults. Issue 4 (5th April 2013) - Yen, Irene H; Gregorich, Steven; Cohen, Alison K; Stewart, Anita
Abstract : Objectives: Typical measures of childhood socioeconomic status (SES), such as father's occupation, have limited the ability to elucidate mechanisms by which childhood SES affects adult health. Mechanisms could include schooling experiences or work opportunities. Having previously used qualitative methods for concept development, we developed new retrospective measures of multiple domains of childhood social and economic circumstances in ethnically diverse older adults. We administered the new measures in a large sample and explored their association with adult SES. Design: We used a cross-sectional survey design with a community sample. Setting: The San Francisco Bay Area in California. Participants: 400 community-dwelling adults from diverse racial/ethnic backgrounds (Whites, African Americans, Latinos and Asians/Pacific Islanders) aged 55 and older (mean=67 years); 61% were women. Primary and secondary outcome measures: We measured attitudes towards schooling, extracurricular activities and adult encouragement and discouragement during the childhood/teen years. Bivariate analysis tested racial/ethnic differences on the various measures. Multivariate regression models estimated the extent to which retrospective circumstances were independently associated with adult educational attainment and adult health. Results: Most of the childhood circumstances measures differed across racial/ethnic groups. In general, Whites reported more positive circumstances than non-Whites. Family financial circumstances, respondent's perception of schooling as a means to get ahead, high school extracurricular activities, summer travel and summer reading were each statistically significantly associated with adult SES. Family composition, age began work, high school extracurricular activities, attitudes towards schooling and adult discouragement were associated with adult health.